Diagnostic value of inflammatory biomarkers of ESR and CRP in differentiating severe and moderate cases of covid-19 patients hospitalized in Shahid Beheshti Hospital in Kashan, Iran, in 2021 - Reza Razaghi; Mansooreh Momen_heravi; Reyhaneh Faghihi; Hamidreza Nahri; Mohammdhasan Fallahzadeh; Mohammad Javad Azadchehr; Mohammad Javad Razaghi (Fiyz̤, 2023)
Background and Aim: The levels of inflammatory biomarkers ESR and CRP are significantly increased in the early stages of the Covid-19 and their levels are related to the severity of the disease. The present study was conducted to determine the diagnostic value of CRP and ESR in COVID-19. Methods: This cross-sectional study was conducted on 287 patients with covid-19 hospitalized in Shahid Beheshti Hospital in Kashan, Iran, in 2021. A questionnaire containing demographic data, clinical symptoms, laboratory findings and final outcome was completed by reviewing the medical records and HIS system. Patients were divided into moderate and severe groups according to the severity of lung involvement in CT scan and oxygen saturation (SPO2). The data were entered into SPSS-16 software and the ESR and CRP levels were compared between the two groups. Moreover, the sensitivity, specificity, positive and negative predictive values, and the cut-off point were determined and the ROC curve was drawn. Results: Out of 287 patients, 151 (52.6%) were women and 136 (47.4%) were men, and the mean age of the patients was 56.14±18.45 years. Hypertension (35.5%) was the most common underlying disease. Shortness of breath (56.8%) and cough (52.3%) were the most common clinical symptoms. In this study, 34.1% of the patients had a severe form of the disease. Finally, 18 patients (6.3%) died. ESR test with a cut-off point of 30, sensitivity of 81.6%, and specificity of 71.4% and CRP test with a cut-off point of 38, sensitivity of 84.7%, and specificity of 82.5% have the necessary accuracy to diagnose the severity of COVID-19. Conclusion: According to the current findings, ESR with a cut-off point of 30 and CRP with a cut-off point of 38 had the necessary diagnostic accuracy to assess the severity of COVID-19. Therefore, in the initial examination of COVID-19 patients, according to the cut-off point of these two important biomarkers, severe cases of the disease should be quickly identified and the necessary treatment measures should be started as soon as possible to prevent poor outcomes.